Development of recommendations for compaction temperatures in the field to acheive denisty and limit as-built permeability of HMA in Wisconsin - Hanz, Andrew; Johnson, Carl M.; Bahia, Hussain; Schmitt, Robert (Wisconsin Highway Research Program, 2009)
The objectives of this study were to (1) evaluate the effect of compaction effort and temperature on densification of HMA in the field and in the lab, (2) quantify the effects of Warm Mix additives on the compaction, and (3) create a dataset capable of determining the effect of as-built density and permeability on asphalt pavement performance. Field testing and loose-mix sampling occurred on 30 unique layers of HMA during the 2007 paving season, and a single Warm Mix project during the 2008 paving season. Loose-mix samples from the construction projects were compacted in the Superpave Gyratory compactor at two pressure settings, 300 kPa and 600 kPa; and at three temperatures of 248, 194, and 140?F. Factors affecting field density gain in rank order were mat temperature, number of roller passes, roller type, vibratory setting, and PG binder grade. Density of 92% Gmm can be achieved, however at lower temperatures, more roller passes are necessary. A 300 kPa pressure yields a density (@ Ndes) about 1.8 % less than 600 kPa at 248?F. The density was reduced by about 0.4% when compacting at 194?F, and 2.4% at 140?F. Aggregate source and fine aggregate angularity had a marginal effect on compactive effort. A moderate correlation was found between lab temperature and field temperature to achieve a mutual density. Higher Ndes mix will require more field passes. A lab and field evaluation of single Warm Mix Asphalt (WMA) E-1 mixture determined that the average final density for WMA and tradition Hot Mix Asphalt were nearly identical. For a similar number of roller passes, 30% RAP content averaged 2.6% greater density values than 40% RAP content. The results of the laboratory evaluation demonstrate that the use of the WMA additive allowed for an increased amount of RAP in the mix without a significant detriment to mixture workability as shown using the CDI. Both the HMA and WMA 30% mixes approached the Superpave criteria of 4% air voids at Ndes over all compaction temperatures, the air void levels in the WMA 40% were considerably lower than the 4% target. A single database was created to model pavement performance and establish specific density and permeability criteria. A stand-alone spreadsheet file is included with
147 p.
Keywords: Asphalt; Performance; Density; Pavement; Permeability